Rozwój rynku usług outsourcingowych w państwach Europy Wschodniej - Butyter, Daniel (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
In the next ten years, it is likely that Eastern Europe will move from being an “emerging destination” to a key destination for outsourced activity. Outsourcing in Eastern Europe is facing many difficulties and challenges. But still during the last 10 years it has been growing rapidly. Romania and Ukraine recorded the largest growth in 2009 in the post-global financial recession period. Hungary, Poland, Belarus, Czech Republic and Bulgaria followed closely. Upcoming trends in the Eastern European outsourcing sphere are likely to be consolidation and an increase in specialized services.
Keywords: struktura rynku; przedsiębiorstwa; outsourcing; technologie informacyjne; handel międzynarodowy